TEMPERATURE-DEFORMATION CRITERION OF OPTIMIZATION OF FINE DRAWING HIGH CARBON WIRE ROUTE - Y. L. Bobarikin; S. V. Avseykov; A. V. Vedeneev; I. N. Radkov (Литьë и металлургия, 2012)
The temperature-deformation criterion of assessment and optimization of routes of the thin high-carbon wire drawing enabling to increase plastic properties of wire at retaining of its durability is offered.